The mPED randomized controlled clinical trial: applying mobile persuasive technologies to increase physical activity in sedentary women protocol - Fukuoka Yoshimi; Komatsu Judith; Suarez Larry; Vittinghoff Eric; Haskell William; Noorishad Tina; Pham Kristin (BMC, 2011)
Abstract Background Despite the significant health benefits of regular physical activity, approximately half of American adults, particularly women and minorities, do not meet the current physical activity recommendations. Mobile phone technologies are readily available, easily accessible and may provide a potentially powerful tool for delivering physical activity interventions. However, we need to understand how to effectively apply these mobile technologies to increase and maintain physical activity in physically inactive women. The purpose of this paper is to describe the study design and protocol of the mPED (mobile phone based physical activity education) randomized controlled clinical trial that examines the efficacy of a 3-month mobile phone and pedometer based physical activity intervention and compares two different 6-month maintenance interventions. Methods A randomized controlled trial (RCT) with three arms; 1) PLUS (3-month mobile phone and pedometer based physical activity intervention and 6-month mobile phone diary maintenance intervention), 2) REGULAR (3-month mobile phone and pedometer based physical activity intervention and 6-month pedometer maintenance intervention), and 3) CONTROL (pedometer only, but no intervention will be conducted). A total of 192 physically inactive women who meet all inclusion criteria and successfully complete a 3-week run-in will be randomized into one of the three groups. The mobile phone serves as a means of delivering the physical activity intervention, setting individualized weekly physical activity goals, and providing self-monitoring (activity diary), immediate feedback and social support. The mobile phone also functions as a tool for communication and real-time data capture. The primary outcome is objectively measured physical activity. Discussion If efficacy of the intervention with a mobile phone is demonstrated, the results of this RCT will be able to provide new insights for current behavioral sciences and mHealth. Trial Registration ClinicalTrials.gov#:NCTO1280812